A INFLUÊNCIA DOS VALORES ORGANIZACIONAIS E A RESILIÊNCIA NOS VÍNCULOS DO TRABALHADOR - NAZARIO, ANA CRISTINA PINTO (2018)
The current labor market, highly competitive and marked by the scarcity of job offers, must be prepared to face the constant pressures for productivity in companies. Work motivation strategies, expressed in organizational values, can be efficient when they directly correspond to the goals and values of the worker. This study investigated the influence of organizational values on the bonds of affective commitment and entrenchment and the moderation of resilience on these relationships. For this, the work was conducted through a single cross-sectional quantitative survey through a printed questionnaire. The data were collected in loco, in a single company located in the metropolitan region of São Paulo. We analyzed 151 questionnaires answered by employees who work in the administrative area of this company. For the hypothesis tests of the study, the analysis of structural equations was performed. It was found a positive relation of the variable organizational value with the variables organizational commitment and organizational entrenchment. The moderation of the resilience variable was not found in the variables organizational values and worker bonds.